1995
DOI: 10.1016/s0090-4295(99)80342-2
|View full text |Cite
|
Sign up to set email alerts
|

The value of screening tests in the detection of prostate cancer. Part I: Results of a retrospective evaluation of 1726 men

Abstract: ABSTRACT-Objectives. The ratio between free and total prostate-specific antigen (PSA) in serum (F/T ratio) was shown to improve the differentiation between prostate carcinoma and benign conditions in selected series of patients. In this study the F/T ratio was analyzed for its ability to improve the specificity of total serum PSA, digital rectal examination (DRE), and transrectal ultrasonography (TRUS) for the detection of prostate cancer in an unselected screening population of men identified in the Rotterdam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
28
1
8

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 11 publications
(1 reference statement)
8
28
1
8
Order By: Relevance
“…In theory, selectively performing a biopsy in men with a higher PSAD would increase the specificity in case of a large prostate and the sensitivity in case of a small gland. While some studies reported that men with PCa had higher PSAD than men with BPH, thereby, 24,25 other studies did not confirm these results. 26,27 In healthy men, most of the serum PSA originates from the transition zone (TZ) epithelium.…”
Section: Psa Densitymentioning
confidence: 92%
“…In theory, selectively performing a biopsy in men with a higher PSAD would increase the specificity in case of a large prostate and the sensitivity in case of a small gland. While some studies reported that men with PCa had higher PSAD than men with BPH, thereby, 24,25 other studies did not confirm these results. 26,27 In healthy men, most of the serum PSA originates from the transition zone (TZ) epithelium.…”
Section: Psa Densitymentioning
confidence: 92%
“…26,27 The use of the FT ratio within patients, e.g., to assess preoperatively the pathologic stage or monitor disease progression, is less well established. 28,29 In our study, no FT ratio treatment effect was found (data not shown).…”
Section: Ratio Of Free and Total Psamentioning
confidence: 99%
“…EARLY DETECTION of prostate cancer is essential to reduce mortality rates, and the serum prostate-specific antigen (PSA) test is currently in wide use as the most effective means of early detection (1). However, although PSA is highly sensitive, specificity is lacking and, when PSA levels are relatively low, cancer is detected in only 30% of biopsies (2).…”
mentioning
confidence: 99%